Tandem high-dose therapy with ifosfamide, epirubicin, carboplatin and peripheral blood stem cell support is an effective adjuvant treatment for high-risk primary breast cancer - Haas, Rainer; Schmid, Hans; Hahn, Uwe; Hohaus, Stefan; Goldschmidt, Hartmut; Murea, S.; Kaufmann, Manfred; Wannenmacher, Michael; Wallwiener, Diethelm; Bastert, Gunther; Hunstein, Werner (European journal of cancer, 1997)
We evaluated the therapeutic efficacy and toxicity of a tandem high-dose therapy with peripheral blood stem cell (PBSC) support in 40 patients with high-risk, primary breast cancer (stage II-III) and involvement of ten or more positive axillary lymph nodes. Their median age was 44 years (range 23-56). Two cycles of cytotoxic chemotherapy with ifosfamide (10000 mg/m2) and epirubicin (100 mg/m2) were administered. Granulocyte colony-stimulating factor (G-CSF) was given to hasten neutrophil reconstitution and to mobilise PBSC during marrow recovery. Leukaphereses were performed following the first and/or second cycle. Tandem high-dose therapy consisted of two cycles with ifosfamide (15 or 12 g/m2) and epirubicin (150 mg/m2), while carboplatin (900 mg/m2) was added for the last 24 patients included. Using an immunocytochemical method, two of 11 patients had cytokeratin-positive tumour cells in three leukapheresis products that were collected following the first G-CSF-supported cycle with ifosfamide and epirubicin, whereas only two harvests obtained following the second cycle in 26 patients contained cytokeratin-positive tumour cells. The number of CD34+ cells/kg re-infused following both high-dose cycles was similar (4.20 ± 0.29 × 106, first cycle and 5.25 ± 0.63 × 106, second cycle), and no notable difference was noted in the speed of haematological reconstitution. An absolute neutrophil count (ANC) of 0.5 × 109/l was reached after a median time of 13 days, while an unsupported platelet count of 20.0 × 109/1 was achieved after a median time of 8 (first cycle) and 9 (second cycle) days post-transplantation. Patients autografted with more than 7.5 × 106 CD34+ cells/kg had platelet counts above 20 × 109/1 within less than 10 days. 6 patients relapsed between 7 and 11 months (median 8 months) post-transplantation. 37 patients are alive and in remission with a median follow-up time of 11 months (range 1-38). This translates into a probability of disease-free survival (DFS) of 77% (95% CI 32-95%) at 38 months. The probability of overall survival is 85%, since 3 patients with local relapse achieved a second complete remission following surgery and involved-field radiotherapy. In conclusion, a sequential high-dose therapy including ifosfamide, epirubicin, carboplatin and PBSC support is well tolerated and effective in patients with high-risk primary breast cancer. Involved-field irradiation should be performed post-transplantation to reduce the risk of local relapse.
Elektronische Reproduktion der Druck-Ausgabe 22. Juli 2002
Gesehen am 19.03.2024